Firm strategy and innovation dynamics - Ilič, Branko (Teorija in praksa, 2021)
Firms of different business strategy types reveal different behavioural patterns in their innovation and business performance while facing various difficulties as they seek to adapt to a turbulent competitive environment. Accordingly, we want to make progress by using the dynamic view, which follows the Schumpeterian perspective of firm behaviour through innovation (business) strategy. We advocate a dynamic approach to the strategic and behavioural patterns influencing business performance that is appropriate for small and mediumsized firms as well as giant corporations in highly competitive industries and catching-up economies. Thus, by combining different theoretical approaches we develop an alternative conceptual "cost-advantage leader-follower" (CALF) model of innovation for when firms are developing cost-cutting process inventions
Keywords: Business policy; Business strategy; catching-up economies; Cost-advantage leader-follower model; dohitevajoče ekonomije; innovation; innovation strategy; inovacijska strategija; model stroškovne prednosti voditelja-zasledovalca; Poslovna politika; poslovna strategija; Strategija; Strategy